2016
DOI: 10.3389/fpls.2016.00629
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids and Response of Plants to Heavy Metals Action

Abstract: Brassinosteroids (BRs) are a widespread group of plant hormones. These phytohormones play a crucial role in the regulation of growth and development of various plant species, and they demonstrate high biological activity. BRs are considered to demonstrate protective activity in the plants exposed to various stresses. Due to rapid industrialization and urbanization, heavy metals have become one of the most important plant stressors. In plants, accumulation of heavy metals beyond the critical levels leads to oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 42 publications
3
63
0
1
Order By: Relevance
“…F I G U R E 5 Effect of HBL spraying intervals, AMF, and their combination on antioxidant enzymes, superoxide dismutase (U g −1 FW hr −1 ), peroxidase (μg g −1 FW min −1 ), catalase (μg g −1 FW min −1 ), and malondialdehyde content (mmol/g FW) of cucumber cultivar CCMC under NaCl (100 mmol/L). Data (means ± SD, n = 3) sharing the same letters above the bars are not significantly different at p = .05 duced and hence lowering the damage caused to membranes (Hayat et al, 2014;Porcel et al, 2012;Rajewska et al, 2016). In our results, the antioxidant activities in cultivar CCMC were higher as compared to cultivar Jinyou 1 # , which were in accordance with Ahmad et al ROS, and the balance between SOD, POD, and CAT is crucial for the stability of ROS production (Ahmad et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…F I G U R E 5 Effect of HBL spraying intervals, AMF, and their combination on antioxidant enzymes, superoxide dismutase (U g −1 FW hr −1 ), peroxidase (μg g −1 FW min −1 ), catalase (μg g −1 FW min −1 ), and malondialdehyde content (mmol/g FW) of cucumber cultivar CCMC under NaCl (100 mmol/L). Data (means ± SD, n = 3) sharing the same letters above the bars are not significantly different at p = .05 duced and hence lowering the damage caused to membranes (Hayat et al, 2014;Porcel et al, 2012;Rajewska et al, 2016). In our results, the antioxidant activities in cultivar CCMC were higher as compared to cultivar Jinyou 1 # , which were in accordance with Ahmad et al ROS, and the balance between SOD, POD, and CAT is crucial for the stability of ROS production (Ahmad et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In our results, the decrease in lipid peroxidation (MDA content) and increase in antioxidant enzymes (SOD, POD, and CAT) in cultivar CCMC as compared to cultivar Jinyou 1 # under combined effect of HBL spraying interval after 15 days and AMF show the additive effect on plants by causing less damage to membranes. It might also be due to the triggering of antioxidant enzymes, which scavenge the ROS produced and hence lowering the damage caused to membranes (Hayat et al., 2014; Porcel et al., 2012; Rajewska et al., 2016). In our results, the antioxidant activities in cultivar CCMC were higher as compared to cultivar Jinyou 1 # , which were in accordance with Ahmad et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the phytohormone groups is brassinosteroids (BRs), which are commonly found in angiosperms, gymnosperms, algae, pteridophyte, and bryophyte at very low concentrations (Bajguz and Tretyn 2003;Stirk et al 2013Stirk et al , 2014Kanwar et al 2017;Bajguz 2019;Zullo and Bajguz 2019). BRs significantly affect the metabolism, growth of both algae and vascular plants, and have a major role in heavy metals stress alleviation (Bajguz and Hayat 2009;Rajewska et al 2016). BRs increase the activity of antioxidant enzymes and the content of antioxidants, protecting plants against unfavorable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Brassinosteroids (BRs) are a widespread group of plant hormones that play a crucial role during plant growth and development (Wang et al ). Furthermore, BRs play a role in abiotic stress responses, such as drought, low temperature, freezing tolerance and heavy metal contamination (Kagale et al , Fowler and Thomashow , Eremina et al , Rajewska et al ). Several recent studies also revealed that BRs participate in pathogen defense responses (Heese et al , Albrecht et al , Belkhadir et al , Wang ), and brassinolide (BL) could induce disease resistance both in tobacco and rice (Nakashita et al ).…”
Section: Introductionmentioning
confidence: 99%